Influence of demographic changes on the number of visits to hospital emergency departments: 13 years' experience - José Lorenzo Guerra Diez; Luis Gaite Pindado; Cristina Álvarez Álvarez; María Teresa Leonardo Cabello; Lino Álvarez Granda; María Jesús Cabero Pérez (Elsevier, 2018)
Objective: The aim of the present study is to describe the trend in volume and age-specific rates in visits to the paediatric emergency department of a university teaching hospital in Cantabria (Spain) from January 2001 to December 2013, and evaluate the influence of population growth on emergency department use. Material and methods: A retrospective study was conducted to analyze all emergency department visits over a 13 year period. Simple and polynomial linear regressions were used to assess the relationship between population size and emergency department attendance rates across 2 age groups (0-2 and 3-14 years). Results: From 2001 to 2013, attendance in the emergency department increased by 14.1%, whereas the paediatric population rose by 26.3%. Rates of presentation per head of population were greatest among those aged <3 years: 1.48 (95% CI 1.40 to 1.56) vs. 0.46 (95% CI 0.44 to 0.48) for the older age group (P < .01). A significant regression equation was found (F[1,11] = 11.2, P < .05) with an R2 = 0.50, showing that population growth produces a continuous rise in the emergency department visits for those aged <3 years. However, ED presentations of patients aged 3-14 years fit a quadratic regression model (R2 = 0.48, F[2,10] = 4.6, P < .05) so increases in population rise ED presentations until an inflection point, after which increases in population will decrease ED visits. Conclusions: Those aged 0-2 years presented a steady increase in ED visits related to population growth, whereas children aged 3-14 years experienced a "saturation of the demand" and a reduction in ED presentations. Resumen: Objetivo: Este estudio evalúa la influencia del crecimiento de la población en la utilización del Servicio de Urgencias Pediátricas de un hospital universitario de Cantabria (España) entre enero de 2001 y diciembre de 2013. Material y métodos: Se realizó un estudio retrospectivo de todas las urgencias ocurridas durante 13 años. Se emplean modelos de regresión lineal simple y polinómica para analizar la relación entre la población y la frecuentación en 2 grupos de edad (0-2 y 3-14 años). Resultados: De 2001 a 2013, las urgencias aumentaron un 14,1% y la población pediátrica un 26,3%. Las tasas de presentación por persona fueron mayores en los menores de 3 años, 1,48 (IC 95% 1,40 a 1,56) frente a 0,46 (IC 95% 0,44 a 0,48) (p < 0,01). El modelo de regresión lineal simple muestra que el crecimiento de la población produce un aumento continuo de las urgencias en los menores de 3 años (R2 = 0,50, F[1,11] = 11,2, p < 0,05). En pacientes de 3 a 14 años la frecuentación se ajusta a un modelo de regresión cuadrática (R2 = 0,48, F[2,10] = 4.6, p < 05) y el incremento de la población aumenta las urgencias hasta alcanzar un punto de inflexión a partir del cual disminuyen. Conclusiones: El grupo de edad de 0 a 2 años presentó un aumento constante en las urgencias relacionado con el crecimiento de la población, mientras que el grupo de 3 a 14 años experimentó una «saturación de la demanda» y una reducción de las visitas.